2015
DOI: 10.1002/ejhf.327
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of subgroups of heart failure patients with preserved ejection fraction with possible implications for prognosis and treatment response

Abstract: Background Patients with heart failure and preserved ejection fraction (HFpEF) have a poor prognosis, and no therapies have been proven to improve outcomes. It has been proposed that heart failure, including HFpEF, represents overlapping syndromes that may have different prognoses. We present an exploratory study of patients enrolled in the Irbesartan in Heart Failure with Preserved Ejection Fraction Study (I-PRESERVE) using latent class analysis (LCA) with validation using the Candesartan in Heart failure: As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

18
269
2
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 225 publications
(292 citation statements)
references
References 35 publications
18
269
2
3
Order By: Relevance
“…A prospective study is needed to determine whether the same medical therapies (renin‐angiotensin aldosterone system inhibitors and beta‐blockers) that have efficacy for reducing progression to symptomatic HF in patients with asymptomatic LV systolic dysfunction would also have comparable efficacy in patients with malignant LVH. Recently, it has been suggested that it is possible to subgroup HFpEF into different phenotypes using machine learning or other algorithms 23, 24. It remains to be determined whether the malignant LVH phenotype may be also able to identify specific patient phenotypes that would be at greater risk to progress to HFpEF among the overall heterogeneous HFpEF cohort.…”
Section: Discussionmentioning
confidence: 99%
“…A prospective study is needed to determine whether the same medical therapies (renin‐angiotensin aldosterone system inhibitors and beta‐blockers) that have efficacy for reducing progression to symptomatic HF in patients with asymptomatic LV systolic dysfunction would also have comparable efficacy in patients with malignant LVH. Recently, it has been suggested that it is possible to subgroup HFpEF into different phenotypes using machine learning or other algorithms 23, 24. It remains to be determined whether the malignant LVH phenotype may be also able to identify specific patient phenotypes that would be at greater risk to progress to HFpEF among the overall heterogeneous HFpEF cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, as expected, CKD was associated with considerably increased risk of anemia, which was minimally attenuated on adjustment. These data suggest that multiple comorbidities independently are associated with and may drive anemia and contribute to one another, and are consistent with the hypothesis of a constellation of comorbidities driving HFpEF [134][135][136] .…”
Section: Anemia and Hfmref And Hfpef (Paper Iii)supporting
confidence: 85%
“…In a recently published exploratory study of patients enrolled in the Irbesartan in Heart Failure with Preserved Ejection Fraction Study (I-PRESERVE), a statistical approach was used to identify HFPEF subgroups and validated using the Candesartan in Heart failure: Assessment of Reduction in Mortality and morbidity (CHARM)-Preserved study, which may potentially differ in prognosis. 16 Clinical profiles and prognosis of the 6 predefined subgroups were similar in the CHARM-Preserved study. The 2 subgroups with the worst event-free survival in both studies were characterized by a high prevalence of obesity, hyperlipidemia, diabetes mellitus, anemia, or renal insufficiency and by female predominance, advanced age, lower body mass index, high rates of atrial fibrillation, valvular disease, renal insufficiency, or anemia, respectively.…”
mentioning
confidence: 77%
“…The 2 subgroups with the worst event-free survival in both studies were characterized by a high prevalence of obesity, hyperlipidemia, diabetes mellitus, anemia, or renal insufficiency and by female predominance, advanced age, lower body mass index, high rates of atrial fibrillation, valvular disease, renal insufficiency, or anemia, respectively. 16 These data, together with the findings of Brzyżkiewicz et al, 2 highlight the need for active searching for the signs and symptoms of HF in patients with certain clinical characteristics and confirmation in further laboratory tests and imaging evaluation. The diagnosis of HFPEF provides information on poor prognosis; however, no treatment has yet been shown to convincingly reduce morbidity and mortality in patients with diastolic HF.…”
mentioning
confidence: 91%
See 1 more Smart Citation